2021
DOI: 10.1111/ijcp.14068
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different platelet‐rich plasma injections in the treatment of mild‐moderate knee osteoarthritis: A systematic review and meta‐analysis

Abstract: Aims This study aimed to compare the efficacy of different numbered sets of injections of platelet‐rich plasma (PRP) in the treatment of mild‐moderate knee osteoarthritis (OA). Methods A comprehensive search in three databases of Cochrane Library, Embase, and PubMed was conducted to find relevant articles that investigated the efficacy of PRP injection therapies in the treatment of mild‐moderate knee OA through August 2020. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Chou et al . 69 for the treatment of mild to moderate knee OA showed that the effect of triple injections of PRP was better than that of single and twice injections, which was consistent with the conclusion of the long-term result of Chouhan et al . 25 The two studies hint to us that the difference in follow-up time of included studies may also be a reason for the inconsistency between our study and the above meta-analysis and the possibility that the chondroprotective effect of triple injections of PRP gradually deteriorates with time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Chou et al . 69 for the treatment of mild to moderate knee OA showed that the effect of triple injections of PRP was better than that of single and twice injections, which was consistent with the conclusion of the long-term result of Chouhan et al . 25 The two studies hint to us that the difference in follow-up time of included studies may also be a reason for the inconsistency between our study and the above meta-analysis and the possibility that the chondroprotective effect of triple injections of PRP gradually deteriorates with time.…”
Section: Discussionsupporting
confidence: 89%
“…It suggests that the antiinflammatory effects of single-injection PRP and multiple-injection PRP were similar in the short term, and multiple injections of PRP may have a chondroprotective effect, but the effect is not long term. Chou et al 69 for the treatment of mild to moderate knee OA showed that the effect of triple injections of PRP was better than that of single and twice injections, which was consistent with the conclusion of the long-term result of Chouhan et al 25 The two studies hint to us that the difference in follow-up time of included studies may also be a reason for the inconsistency between our study and the above meta-analysis and the possibility that the chondroprotective effect of triple L Chen, S Jin et al…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PRP on cell proliferation and ECM formation could lead to restoring cartilage damage in the early stages of OA. Recent evidence has suggested that PRP therapy is clinically more effective in patients with mild or moderate knee OA 73,74 . It is very difficult for PRP to restore the damage generated in the cartilage or synovium in people with more severe OA.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled improvements among different injection therapies were investigated recently. Chou et al discovered that 3-injection PRP therapy in the treatment of mild-to-moderate knee OA had the best efficacy for pain relief and function improvement compared to one- and 2-injection therapies ( Chou and Shih, 2021 ). To date, the preparation and usage of PPR were not unified, the dosage and frequency of use were also different, and the follow-up time of clinical research was short, so a consensus on the curative effect of PRP had not been formed.…”
Section: Discussionmentioning
confidence: 99%